2016
DOI: 10.1038/srep36287
|View full text |Cite
|
Sign up to set email alerts
|

Serological diagnosis of pneumocystosis: production of a synthetic recombinant antigen for immunodetection of Pneumocystis jirovecii

Abstract: Diagnosis of Pneumocystis pneumonia (PcP) relies on the detection of P. jirovecii in respiratory specimens obtained by invasive techniques. Thus, the development of a serological test is urgently needed as it will allow the diagnosis of PcP using blood, an inexpensive and non-invasive specimen. This study aims to combine the production of a multi-epitope synthetic recombinant antigen (RSA) and an ELISA test for detection of anti-P. jirovecii antibodies, in order to develop a new approach for PcP diagnosis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…Recently, studies showed that a technology based on synthetic amino acid sequences, designed to hold more than one reactive region of the selected antigens, could enhance the immunological diagnosis of Toxoplasma gondii (Dai et al, 2012(Dai et al, , 2013. Therefore, in our previous study, this research group designed a recombinant synthetic antigen (RSA) with three antigenic regions of the Msg protein, in order to standardize and enhance the detection of reactive antibodies against P. jirovecii (Tomás et al, 2016). In this single antigenic tool, several proven reactive and conserved fragments of the Msg were used, improving its immunogenic power and consequently its application as an anti-P. jirovecii antibody detection tool (Tomás et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, studies showed that a technology based on synthetic amino acid sequences, designed to hold more than one reactive region of the selected antigens, could enhance the immunological diagnosis of Toxoplasma gondii (Dai et al, 2012(Dai et al, , 2013. Therefore, in our previous study, this research group designed a recombinant synthetic antigen (RSA) with three antigenic regions of the Msg protein, in order to standardize and enhance the detection of reactive antibodies against P. jirovecii (Tomás et al, 2016). In this single antigenic tool, several proven reactive and conserved fragments of the Msg were used, improving its immunogenic power and consequently its application as an anti-P. jirovecii antibody detection tool (Tomás et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in our previous study, this research group designed a recombinant synthetic antigen (RSA) with three antigenic regions of the Msg protein, in order to standardize and enhance the detection of reactive antibodies against P. jirovecii (Tomás et al, 2016). In this single antigenic tool, several proven reactive and conserved fragments of the Msg were used, improving its immunogenic power and consequently its application as an anti-P. jirovecii antibody detection tool (Tomás et al, 2016). In the present study, this RSA was used in combination with a new RSA, produced based on the immunogenic behavior of P. jirovecii Kex1 protein.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations